2019
DOI: 10.1111/ijcp.13335
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dapagliflozin, an SGLT2 inhibitor, on serum levels of soluble dipeptidyl peptidase‐4 in patients with type 2 diabetes and non‐alcoholic fatty liver disease

Abstract: Aims Soluble dipeptidyl peptidase‐4 (sDPP‐4) is secreted by hepatocytes and induces adipose tissue inflammation and insulin resistance. Sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors can improve hepatic steatosis by inhibiting hepatic de novo lipogenesis. We investigated the effects of dapagliflozin (an SGLT2 inhibitor) on serum levels of sDPP‐4 in patients with type 2 diabetes and non‐alcoholic fatty liver disease (NAFLD). Methods Fifty‐seven patients with type 2 diabetes and NAFLD were randomized to a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 29 publications
2
63
0
1
Order By: Relevance
“…13 Concerning diabetes-associated liver disease, SGLT2 inhibitors such as ipragliflozin, 14,15,18,20 remogliflozin etabonate, 17 empagliflozin 16 and luseogliflozin 19 have been reported to be able to prevent and/or to alleviate the development of NAFLD in several experimental models of NAFLD. Besides, ipragliflozin 20 and dapagliflozin 44 were also reported to ameliorate steatosis-associated hepatic enzymatic markers in T2D subjects with NAFLD. However, these studies investigated neither the effects of a dual SGLT1/2 inhibitor nor the NAFLD relationship with hepatic glucose metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…13 Concerning diabetes-associated liver disease, SGLT2 inhibitors such as ipragliflozin, 14,15,18,20 remogliflozin etabonate, 17 empagliflozin 16 and luseogliflozin 19 have been reported to be able to prevent and/or to alleviate the development of NAFLD in several experimental models of NAFLD. Besides, ipragliflozin 20 and dapagliflozin 44 were also reported to ameliorate steatosis-associated hepatic enzymatic markers in T2D subjects with NAFLD. However, these studies investigated neither the effects of a dual SGLT1/2 inhibitor nor the NAFLD relationship with hepatic glucose metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, multivariate analysis indicated that the increase in %△HIC CIR was independently correlated with the increase in %△active GLP‐1 AUC 0‐120min (Table S7; see Supporting Information). Although it is difficult to clarify this mechanism in the present study, a previous study indicated that dapagliflozin administration reduced the serum level of soluble dipeptidyl peptidase‐4 (sDPP‐4) in patients with type 2 diabetes with non‐alcoholic FL disease; therefore, a decrease in serum sDPP‐4 via an SGLT2‐i may be partly involved.…”
Section: Discussionmentioning
confidence: 99%
“…Attenuation of the glucose‐lowering effect of DPP‐4 inhibitors in obese patients can be partially explained by the higher circulating level of a hepatokine, soluble DPP‐4/CD26 . The reduction in the high liver enzyme levels after treatment with SGLT2 inhibitors was associated with a decrease in serum soluble DPP‐4, suggesting that reducing serum soluble DPP‐4 levels by SGLT2 inhibitors can restore the glucose‐lowering effect of DPP‐4 inhibitors.…”
Section: Discussionmentioning
confidence: 99%